Dissecting the inhibitory activity of Burkholderia orbicola against Gram-positive and - negative multidrug-resistant bacteria - Leslie-Mariana Morales-Ruíz; Anuar Salazar-Gómez; Álvaro-Omar Hernández-Rangel; Jeniffer-Chris Kerber-Díaz; María-Elena Vargas-Díaz; J. Antonio-Ibarra; Fernando-Uriel Rojas-Rojas; Paulina Estrada-de los Santos (PLoS ONE, 2025)
The genus Burkholderia is currently recognized for producing several antimicrobial compounds with potential applications in developing novel treatments for infectious diseases, including those caused by multidrug-resistant (MDR) bacteria. This study aimed to investigate the ability of Burkholderia orbicola TAtl-371T and CACua-24 to inhibit the growth of MDR human pathogens and to analyze the chemical composition of active extracts from cultures of these strains to identify putative compounds associated with their activity. The double-layer agar technique was used to evaluate the antimicrobial activity of B. orbicola strains. Sequential solvent extraction with hexane, dichloromethane, ethyl acetate, and methanol was conducted on B. orbicola cultures, and the active extract was analyzed by bioautography and fractionated using preparative thin-layer chromatography. Putative antimicrobials in the active fraction were identified through 1H, 13C NMR, and mass spectrometry. B. orbicola strains inhibited several MDR strains of Acinetobacter baumannii, Klebsiella pneumoniae, Pseudomonas aeruginosa, Escherichia coli, and Staphylococcus aureus on double-layer agar probes, displaying inhibition halos ranging from 5 to 41 mm. The hexane extract showed the best inhibitory activity against MDR strains, except for P. aeruginosa strains. Analysis through thin-layer chromatography and bioautography revealed a tailing spot with antimicrobial activity. The spectroscopic analysis of this tailing spot revealed the presence of the siderophore fragin. This fragin-containing fraction inhibited the MDR A. baumannii (1024 µg/mL), K. pneumoniae 903137 (128 µg/mL), E. coli (256 µg/mL), and S. aureus (128 µg/mL), but no effect was observed against P. aeruginosa. This fraction also inhibited yeasts of the species Candida albicans and Nakaseomyces glabratus, suggesting an antimicrobial spectrum that extends beyond MDR bacteria. The genomic sequence analysis of strains TAtl-371T and CACua-24 revealed a cluster of 7 genes, resulting in the same organization and over 99% similarity to the fragin genes reported for Burkholderia cenocepacia H111. This study highlights the potential of B. orbicola to produce fragin and its potential activity against MDR bacteria that affect human health worldwide.